ETNISITAS, POLITIK, DAN PEMBANGUNAN NEGARA BANGSA DI MALAYSIA - Mohammad Maiwan (Jurnal Ilmiah Mimbar Demokrasi, 2017)
Malaysia is a multiethnic country, in which ethnic factors as the basis of political interests. So far, efforts to create national integration have been directed at strengthening relations between ethnic groups and creating a political balance for all peoples. Efforts to build a nation state are conducted through policy: political cooperation, economic affirmation for ethnic Malays, education, and strengthening the position of Malay as the national language. The challenge to the nation state development in Malaysia emerged during the economic crisis of 1998. The conflict brought political divisions among Malaysians, especially Malays. After Mahathir Mohamad's reign, efforts to promote national unity were carried out by introducing a moderate and tolerant concept of Islam Hadhari. During the leadership of Najib Razak, efforts to build a nation state were undertaken under the idea of One Malaysia. One of the challenges of developing a nation today is: The widening of gaps, racial prejudices, increased group identity, intolerance and corruption.